Adolescent tracheal intubation in an adult urban emergency department: a retrospective, observational study. (December 2017) - Hale, James J.; Lynch, Stephen; Ray, David C.; Reid, Lindsay A.
Abstract : Objectives: Tracheal intubation is the cornerstone of advanced emergency airway management in children and adults and there is good-quality data characterizing intubation in both groups. There are, however, few published studies on emergency tracheal intubation in adolescents. We carried out an observational study to characterize tracheal intubation in adolescents. Methods: We analysed data from a previously collected Emergency Department Intubation Registry. We included all attempts at tracheal intubation performed in our adult emergency department between 1999 and 2011. We recorded the indication for intubation, the staff involved, the technique and drugs used, and the rates of successful intubation and adverse events. We classified patients into three age groups: 13–16 years (adolescent), 17–24 years (young adult) and at least 25 years (older adult). Results: Trauma was the most common indication for intubation in adolescents, and rapid sequence induction was used in 88% of cases. Ninety-nine percent of tracheal intubations in adolescent patients were successful on the first or the second attempt, no adolescent underwent more than three attempts and none required a surgical airway. The initial intubation attempt in adolescents was more likely to be performed by an anaesthetist ( P <0.005). The first attempt success rate was higher ( P <0.01) and adverse event rate was lower ( P <0.05) in adolescents than in adults. Hypotension was the only adverse event recorded in adolescents; this occurred in three patients (4.5%). Conclusion: Our findings suggest that the airway in adolescent patients can be managed successfully and safely in an adult emergency department where there is close collaboration between anaesthetists and emergency physicians.